BEYOND THE NOSE: A CLINICAL INSIGHT INTO NASOPHARYNGEAL FOREIGN BODY IMPACTION: A CASE REPORT - Dr. Manisha Naiknaware, Dr Rajendra Bohra, Dr. Susan Pallicken, Dr. Khushboo Jain (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Foreign body lodgement in the maxillary sinus, nose and nasopharynx is a rareoccurrence in mentally sound adults. We report the case of a patient who presented with a wooden stem impacted in the right maxillary